A1.28 Synovial fibroblasts suppress TH1, but not TH2 or TH17 cells, through tryptophan metabolism. (13th February 2015) - Tykocinski, LO; Lauffer, AM; Bohnen, A; Krienke, S; Tretter, T; Adam, I; Mohapatra, SR; Saikali, P; Löhning, M; Neidhart, M; Gay, S; Oezen, I; et al.
Abstract : Background and objectives: Fibroblasts strongly participate in the initiation and modulation of immune responses. The development of rheumatoid arthritis (RA) is linked to functional changes of synovial fibroblasts (SF) and a local infiltration of immune cells such as T lymphocytes. So far, little is known about the cross-talk between SF and T cells under normal and pathological conditions. Here, we analysed the influence of normal SF as well as of RASF on the activation, proliferation and cytokine production of T helper (Th) cell subsets in vitro . Materials and methods: SF were isolated from synovectomy tissues of patients with osteoarthritis (OA) or RA. Th1, Th2 and Th17 cells were differentiated in vitro or directly isolated from peripheral blood. Complete Th cells or Th cell subsets were stimulated in the presence or absence of SF, in direct contact or separated by transwell chambers. T cell proliferation was measured by [ 3 H] thymidine incorporation or by PKH-26 labelling. Secretion of cytokines and prostaglandin E2 (PGE2) was quantified by ELISA. MRNA levels of matrix metalloproteases (MMPs) and indoleamine 2, 3-dioxygenase 1 (IDO1) were quantified by real-time PCR. Tryptophan and kynurenine amounts were detected by HPLC. IDO1 activity was blocked by 1-L-methyl-tryprophan (1-L-MT), cyclooxigenases 1 and 2 were inhibited by indomethacin. Results: SF supported the activation of T cells at early time points of co-culture and in return the T cells induced the expression of interleukin (IL)-6, IL-8, MMP1 and 3, as well as of PGE2 and IDO1 by the SF. In the end, the stimulated SF strongly suppressed the secretion of interferon (IFN)-g and the proliferation of co-cultured Th cells in a cell contact-independent manner. Strikingly, Th1 cells, but not Th2 or Th17 cells, were affected. A decrease of tryptophan and an increase of kynurenines in the culture supernatants correlated with the T cell suppression. Blockade of IDO1 completely restored the Th cell proliferation, but not the IFNg secretion, indicating that the suppression of T cell proliferation by SF is mediated by tryptophan metabolism. Importantly, RASF had a weaker T cell suppressive capacity compared to OASF. Conclusions: The suppression of activated T cells by SF through tryptophan metabolism may play an important role in preventing inappropriate T cell responses under normal conditions. Th17 cells that escape the suppression by SF and the inferior efficiency of RASF to restrict T cell proliferation may likely support the initiation and propagation of synovitis in RA.